A tale of spilled stones - Goja, Shikha; Kushwaha, Swapnil Singh (International Surgery Journal, 2019)
Cholecystectomies are one of the commonest surgeries done in India. Gallbladder perforation and stone spillage is common and occurs in 15 to 40% of laparoscopic and 5 to 20% of open cholecystectomy procedures. In up to a third of these cases, stones are not retrieved and complications can arise many years post-operatively. In majority of cases these lost stones either in laparoscopic or open surgery remain silent but rarely can become symptomatic and cause range of complications like intra-abdominal abscesses, empyema, abdominal wall abscesses, cutaneous sinus tract and bladder fistulas. Diagnosis can be difficult and patients may present to many specialties within medicine and surgery. We seek to present our case and on a rare complication and management of one such “lost” stone.